China’s pattern of growth moving to sustainability and reducing inequality - Guo, Yating; Rosland, Anitha; Ishak, Suryati; Muhamad Senan, Mohamad Khair Afham (Taylor and Francis Group, 2022)
The objective of this study was to identify the pattern of economic growth of China by identifying the factors that are contributing to sustainability and reducing inequality in the Chinese communities. The role of sustainable development goals has become critical for even the non- democratic country because inequality is also found in China which is rapidly increasing due to overpopulation and other factors. In this study, the questionnaire was developed on the Likert scale to collect the data from the economists to test the relationship between the hypotheses. The sample size for this study was 330 from the selected population of 800 people with a response rate of 45%. The study concludes that there is a critical role of sustainable development goals, sustainable economic policy, and labor productivity in the growth of China's economy. Further, this study also demonstrates that the Chinese government must focus on sustainability to reduce inequality in society. Significantly, this study provides a detailed insight into the relationship of factors that are contributing to China’s economic growth that was not discussed earlier in the Chinese economic context.